Values, rights, and the new morality, do they conflict? - Nelson, Jack L. (Englewood Cliffs, N.J. : Prentice-Hall, 1977)
Discusses issues facing contemporary society arising from conflict between moral standards and personal behavior.
Bibliography: page 115-118.
Filmography: page 118-120.
Keywords: Social values; United States -- Moral conditions